SISTEM INFORMASI PERSEWAAN KENDARAAN BERBASIS MULTIUSER - Lina Mulyani; Maya Utami Dewi (Multimatrix, 2019)
AbstrakRadian Rent a Car Semarang, one of developing transportation service provider, faces obstacles in processing data and information since its customer is increasing year to year. The obstacles are spending many times to make report of car damage in mechanic division because weekly or monthly car maintenance data has to be checked one by one, there is not any accounting report that is directly given to the owner since it take long time to look for and reprocess the data, and taking long time to searching carâ€™s receipt and maintenance archive as there are so many unprocessed data that are still in stack of archive. It is not impossible if the processing of tenant data and information use undergoing system, it will take long time to fix the emerged error.In order to increase the performance and to ease and accelerate data and information processing, the writer try to create multiuser based information system of car rental by using Microsoft Visual Foxpro 9.0 software and database of its Microsoft Visual Foxpro to overcome the weakness of the undergoing system of car rental. Microsoft Visual Foxpro 9.0 is program that is designed to help the company to accelerate and ease data processing activity with minimal error level and efficient cost and power. The data include car data, tenant data, user data, and rental car data. This program is able to make data processing job be effective and efficient, to cut time spending to process the data, to minimize error input data, and to organize the data saved in one databaseÂ Keywords: database, processing data, rental, data and information